1991
DOI: 10.1002/app.1991.070420123
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized PVC films/petroleum oils: The effect of ultraviolet irradiation on plasticizer migration

Abstract: SYNOPSISPlasticizer migration from flexible poly (vinyl chloride ) comprises an important aspect, especially when packaging foodstuffs and pharmaceuticals. Much of the published work has been intended either to correlate migration into simulants with that into foods or to study migration into simpler extractants, enabling the various parameters involved in migration to be studied in isolation. According to the latter approach, the migration of dioctyl phthalate into petroleum oils has been studied already in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…[10][11][12][13][14][15] The knowledge of the transport parameters of the surrogate-polymer system, and especially of the diffusion coefficient, D, therefore becomes of critical importance. Since, in practice, diffusion experiments are difficult to perform and time consuming, it would be very useful to be able to predict diffusivity through modeling for such surrogate-polymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] The knowledge of the transport parameters of the surrogate-polymer system, and especially of the diffusion coefficient, D, therefore becomes of critical importance. Since, in practice, diffusion experiments are difficult to perform and time consuming, it would be very useful to be able to predict diffusivity through modeling for such surrogate-polymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was quite common in previous studies on plasticizer migration into liquid environments. [5][6][7]16,17 Furthermore, it was proposed that counterdiffusion can be separated into two distinct processes comprising liquid transfer into and out of the PVC sheets. Thus, the maximum of the counterdiffusion curve is considered to be the equilibrium value for the sorption (or penetration) process, as well as the initial value of the desorption process.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the maximum of the counterdiffusion curve is considered to be the equilibrium value for the sorption (or penetration) process, as well as the initial value of the desorption process. 16,17 In the sorption data, the Fickian approximation for short times seems to be appropriate because the liquid penetration process occurs within a period of a few days. On the contrary, the desorption stage is certainly a long-term process that requires the long-term approximation of Fick's law for a satisfactory fitting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of plasticizers such as dioctyl phthalate (DOP) on the mechanical properties was investigated [17]. Plasticizer migration from flexible PVC comprises an important aspect, especially when this type of PVC is used in packaging foodstuff and pharmaceuticals [18]. The workers studied the effect of UV irradiation on the migration of DOP from the polymer matrix, and they found that this migration was reduced or even prevented by the influence of UV irradiation.…”
Section: Introductionmentioning
confidence: 99%